2022
DOI: 10.1017/s1366728922000323
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic engagement of cognitive control in intra-sentential code-switching during comprehension

Abstract: This study investigated whether the deployment of cognitive control was modulated by the intra-sentential code-switching types during comprehension. L1-dominant Chinese–English bilinguals were administered a self-paced reading task in two reading contexts – namely, alternation context and dense code-switching context. We assessed language switch cost and reversed language dominance effect in the self-paced reading task and examined how these language control measures related to domain-general inhibition and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In the present study, participants’ language proficiency was assessed using the Oxford Placement Test (OPT) and a self-rating questionnaire. The OPT provided an objective measure of English (L2) proficiency ( Jiao et al, 2020 ; Jiang et al, 2022 ), with higher scores indicating greater proficiency. The mean score of OPT of all participants was 34.21 (SD = 3.89).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, participants’ language proficiency was assessed using the Oxford Placement Test (OPT) and a self-rating questionnaire. The OPT provided an objective measure of English (L2) proficiency ( Jiao et al, 2020 ; Jiang et al, 2022 ), with higher scores indicating greater proficiency. The mean score of OPT of all participants was 34.21 (SD = 3.89).…”
Section: Methodsmentioning
confidence: 99%
“…Code switching between English and other languages has been a focal point in numerous studies. One such investigation by Jiang et al (2023) employed a self-paced reading task to explore how intra-sentential code switching affects Chinese-English bilinguals' cognitive control during language comprehension. Their findings revealed a larger asymmetry in switch costs in alternation contexts compared to dense code-switching contexts.…”
Section: Analysis Of Hot Topicsmentioning
confidence: 99%
“…The most likely explanation is that the local language control mechanism is dynamic and may exhibit varying degrees of cross-language competition, depending on a host of factors such as the task paradigm (e.g., voluntary language switching versus language switching; [67]), language contexts (e.g., alternation context versus dense code switch context; [29]), cue-stimulus interval [16,31], response-cue intervals [16,35], types and numbers of stimuli [32], individual language proficiency (e.g., [1,5]), and individual general cognitive control abilities (e.g., [22,33]).…”
Section: Similarities and Differences In Control Mechanisms Between B...mentioning
confidence: 99%
“…Although many studies have observed (one or more of) these effects (i.e., [3,5,13,27]), many studies have not reported any of these effects [28]. The decreased robustness of these effects may be due to the fact that they were modulated by language proficiency (e.g., [1,5]), language contexts (e.g., alternation context versus dense code switch context; [29]), preparation time (e.g., [16,30,31]), types and numbers of stimuli [30,32], and individual general cognitive control (e.g., [22,33]). Collectively, these studies suggest that linguistic task-related parameters and cognitive abilities may be key factors in revealing the cognitive nature of bilingual language control.…”
Section: Introductionmentioning
confidence: 99%